2021
DOI: 10.1186/s13014-020-01701-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoradionecrosis of the jaw in patients with head and neck squamous cell carcinoma

Abstract: Background To evaluate factors associated with osteoradionecrosis of the jaw (ORNJ) in patients with head and neck squamous cell carcinoma (HNSCC), focusing on jaw-related dose–volume histogram (DVH) parameters. Methods We retrospectively reviewed the medical records of 616 patients with HNSCC treated with curative-intent or postoperative radiation therapy (RT) during 2008–2018. Patient-related (age, sex, history of smoking or alcohol use, diabetes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 36 publications
3
76
1
2
Order By: Relevance
“…Therefore, some experts aim to defer systemic therapies by MDT. Androgen deprivation therapy-free survival (ADT-FS) was introduced as a new endpoint and reported by some authors, ranging between 7 and 66 months with MDT [ 13 ]. Furthermore, the STOMP randomized phase II trial showed a prolonged ADT-FS compared to surveillance (21 vs. 13 months) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, some experts aim to defer systemic therapies by MDT. Androgen deprivation therapy-free survival (ADT-FS) was introduced as a new endpoint and reported by some authors, ranging between 7 and 66 months with MDT [ 13 ]. Furthermore, the STOMP randomized phase II trial showed a prolonged ADT-FS compared to surveillance (21 vs. 13 months) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive oligometastatic prostate cancer patients treated with MDT to bone metastases between November 2011 and December 2019 at the University Hospital LMU Munich were retrospectively analyzed. Men with histologically confirmed prostate cancer who received definitive-intent radiotherapy to five or less bone metastases were eligible for this study [ 13 ]. Both castration sensitive and castration resistant patients were included, and patients were allowed to have concomitant ADT administered during MDT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medial field border of WBI for the normal inhalation and normal exhalation scans were reported to move average of 6 mm anteriorly and 3 mm posteriorly compared with the free-breathing position, respectively [ 25 ]. Ono et al reported that the AP motion was 1.36 ± 0.94 (0.14–5.28) mm in left-sided breast cancer patients treated with WBI using deep inspiration breath-hold [ 26 ]. In our study, no method of controlling for respiration was applied and the set up errors in AP direction was 2.75 ± 1.56 cm in free breathing, which was much lager than Yuka Ono et al reported [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics is an emerging field developing descriptive or predictive computational models for image analyses to improve individualized diagnosis or treatment selection [ 13 , 14 , 15 ]. Radiomics relies on the extraction of a large amount of quantitative imaging features (radiomic features) such as first-order statistics (histogram and shape parameters), and second or higher-order statistics simultaneously providing spatial and voxel intensity information (texture features).…”
Section: Introductionmentioning
confidence: 99%